Longitudinal outcome and recovery of social problems after pediatric traumatic brain injury (TBI): Contribution of brain insult and family environment. Issue 1 (29th December 2015) - Ryan, Nicholas P.; van Bijnen, Loeka; Catroppa, Cathy; Beauchamp, Miriam H.; Crossley, Louise; Hearps, Stephen; Anderson, Vicki
Abstract: Pediatric traumatic brain injury (TBI) can result in a range of social impairments, however longitudinal recovery is not well characterized, and clinicians are poorly equipped to identify children at risk for persisting difficulties. Using a longitudinal prospective design, this study aimed to evaluate the contribution of injury and non‐injury related risk and resilience factors to longitudinal outcome and recovery of social problems from 12‐ to 24‐months post‐TBI. 78 children with TBI (injury age: 5.0–15.0 years) and 40 age and gender‐matched typically developing (TD) children underwent magnetic resonance imaging including a susceptibility‐weighted imaging (SWI) sequence 2–8 weeks post‐injury ( M = 39.25, SD = 27.64 days). At 12 and 24‐months post‐ injury, parents completed questionnaires rating their child's social functioning, and environmental factors including socioeconomic status, caregiver mental health and family functioning. Results revealed that longitudinal recovery profiles differed as a function of injury severity, such that among children with severe TBI, social problems significantly increased from 12‐ to 24‐months post‐injury, and were found to be significantly worse than TD controls and children with mild and moderate TBI. In contrast, children with mild and moderate injuries showed few problems at 12‐months post‐injury and little change over time. Pre‐injury environment and SWI did not significantly contribute to outcome at 24‐months, however concurrent caregiver mental health and family functioning explained a large and significant proportion of variance in these outcomes. Overall, this study shows that longitudinal recovery profiles differ as a function of injury severity, with evidence for late‐emerging social problems among children with severe TBI. Poorer long‐term social outcomes were associated with family dysfunction and poorer caregiver mental health at 24‐months post injury, suggesting that efforts to optimize the child's environment and bolster family coping resources may enhance recovery of social problems following pediatric TBI.